Հայր Ղևոնդ Ալիշանը արվեստում - Քամալյան, Մարգարիտա (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
Образ известного ученого, поэта и педагога отца Гевонда Алишана (1820–1901) увековечили в живописи, скульптуре и графике армянские и иностранные художники и скульпторы. Алишан в работах Аршака Фетваджана, Ноэ Бординьона и Ефрема Саваяна – ученый-интеллигент. Интересны графические портреты ученого, напечатанные в газете «Ардзаганк» (Тифлис, художник Арутюн Шамшинян), в «Альбоме армянских деятелей» (Тифлис, художник Пол Асатур), а также в журнале «Гегуни» (Венеция, художник Симон Нахапет). The image of a renowned scientist, poet and pedagogue Ghevond Alishan (1820–1901) has been immortalized in painting, sculpture and graphic art by Armenian and foreign painters and sculptors. In the works of Arshag Fetvadjyan, Noy Bordignon and Yefrem Savayan Alishan is a scientist-intellectual. The scientist’s graphic portraits are interesting, which were published in “Ardzaganq” newspaper (Tiflis, painter Harutyun Shamshinyan), in the “Album of portraits of eminent persons of Armenian nation” (Tiflis, painter Paul Assatour), as well as in “Geghuni” journal (Venice, painter Simon Nahabed).
Keywords: Literature